2014
DOI: 10.1111/jnp.12043
|View full text |Cite
|
Sign up to set email alerts
|

Functional mapping of left parietal areas involved in simple addition and multiplication. A single‐case study of qualitative analysis of errors

Abstract: All electrostimulation studies on arithmetic have so far solely reported general errors. Nonetheless, a classification of the errors during stimulation can inform us about underlying arithmetic processes. The present electrostimulation study was performed in a case of left parietal glioma. The patient's erroneous responses suggested that calculation was mainly applied for addition and a combination of retrieval and calculation was mainly applied for multiplication. The findings of the present single-case study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, while it is clear that mental calculation is connected to several cognitive processes, information about cerebral areas involved in different calculation processes is still relatively limited. Indeed, despite several attempts to investigate the causal role of brain regions involved in simple mental calculation (e.g., Andres et al, 2011;Della Puppa et al, 2015b;Maurer et al, 2015;Salillas et al, 2012), few studies have addressed this issue on more complex mental calculation (e.g., De Smedt et al, 2009;Grabner et al, 2015). This issue is particularly important because of a crucial difference between simple and complex mental calculation that is not merely quantitative.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, while it is clear that mental calculation is connected to several cognitive processes, information about cerebral areas involved in different calculation processes is still relatively limited. Indeed, despite several attempts to investigate the causal role of brain regions involved in simple mental calculation (e.g., Andres et al, 2011;Della Puppa et al, 2015b;Maurer et al, 2015;Salillas et al, 2012), few studies have addressed this issue on more complex mental calculation (e.g., De Smedt et al, 2009;Grabner et al, 2015). This issue is particularly important because of a crucial difference between simple and complex mental calculation that is not merely quantitative.…”
Section: Introductionmentioning
confidence: 99%
“…With the same goal, recent studies conducted with direct cortical electrostimulation (DCE) found a role of specific RH areas in simple addition and multiplication (Della Puppa et al, 2013;Della Puppa et al, 2015a;Della Puppa et al, 2015b;Duffau et al, 2002;Roux et al, 2009;Semenza et al, 2016) and subtractions (Yu et al, 2011). Finally, by means of a technique similar to rTMS and DCE (i.e., transcranial direct current stimulation, tDCS) and focusing on the acquisition of mathematical knowledge, Grabner and colleagues (2015) demonstrated that the left posterior parietal cortex is causally involved in arithmetic learning of two-digit operations.…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of the right parietal lobe impaired simple subtraction ( Yu et al, 2011 ). Later studies identified positive sites in the right hemisphere also in addition, in the supramarginal gyrus, and in multiplication, in the angular gyrus, the supramarginal gyrus, the interparietal sulcus and the superior parietal lobule ( Della Puppa et al, 2013 , 2015 ). Crucial information came from the analysis of substitution errors (omissions were less than 5%; Semenza et al, 2017 ).…”
Section: Lesion Casesmentioning
confidence: 97%
“…1c, d) were shown just anteriorly [1,2] and laterally [3] to the tumor; 1 site involved in multiplication (Fig. 1e) was shown just medially to the tumor.…”
Section: Dear Editormentioning
confidence: 99%
“…
We recently reported our experience on functional mapping for calculation processing [1][2][3]. The numerical processing is a crucial function in daily life and its preservation can be achieved in patients undergoing neurosurgery.
…”
mentioning
confidence: 99%